Immigration and labor: towards a model of analysis. Application to the construction sector. - Ioé, Colectivo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article recovers the main questions raised in a recent research on the incidence of foreign workers in the construction sector. The authors present their general approach to the complex issue of labour markets and immigration and the result of using this approach for the analysis of the construction sector. The purpose of the authors is to bring up for debate the main elements of the line of work which they are now also applying to the study of the hotel business, analyzing specific labour areas that enable us to get a more detailed view of the social and labour processes as well as to identify the different segments of the workforce, placing in them the part played by the «foreign status factor» in a more precise way.